Association between knowledge, attitude, and behavior on nutritional anemia among female undergraduate students: a cross-sectional study - Artanti Emiliana; Adistha Eka Noveyani; Septi Nur Rachmawati (AcTion: Aceh Nutrition Journal, 2025)
Anemia is a common health issue among adolescent girls, including female students. Adolescents tend to experience various behavioral changes that affect their health, including anemia. Good health behaviors are shaped by positive attitudes and knowledge. This study aimed to analyze the relationship between knowledge, attitude, and behavior related to nutritional anemia and the incidence of anemia among female undergraduate students at the Jember Regency. This observational study used a cross-sectional design. This study was conducted between February and May 2024 at the University of Jember. The sample consisted of 109 respondents, selected through multistage sampling. Data were collected through questionnaires, anthropometric measurements, and hemoglobin levels using point-of-care testing (POCT) blood tests. Data analysis was performed using the chi-squared test. Significant relationships were found between behaviors related to anemia and anemia (p=0,009; PR= 1,58), knowledge of anemia and anemia (p=0,013; PR= 1,45), and attitudes toward anemia and anemia (p=0,013; PR= 1,52). These findings indicate that behavior, knowledge, and attitudes related to anemia are associated with the incidence of anemia.  We expected adolescents to be more proactive in preventing anemia and in seeking more information about it. Educational institutions should integrate anemia prevention education (nutrition, importance of iron supplements, and healthy eating patterns) into campus curricula. Moreover, they provide iron-rich foods and vitamin C source meals for faculty canteens.